2011
DOI: 10.1007/s11739-011-0621-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of virulent Helicobacter pylori strains in patients affected by idiopathic dysrhythmias

Abstract: Helicobacter pylori virulent strains have been shown to affect cardiovascular diseases through molecular mimicry mechanisms. Silent autoimmune myocarditis has been hypothesized to be the cause of idiopathic dysrhythmias (IA). The aim of this study is to assess the prevalence of virulent H. pylori strains in patients affected by IA. In this study,54 patients (40 men, mean age 44 ± 17 years) affected by IA and 50 healthy subjects (34 men, mean age 45 ± 9) were evaluated. IA, defined as dysrhythmias with no evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…In contrast, one study of our group on a possible role of virulent strains of H. pylori on patients with idiopathic dysrhythmia showed positive findings [10]. In particular, we found a higher prevalence of both CagA and VacA-positive H. pylori strains in patients with idiopathic dysrhythmia compared to controls [10].…”
Section: Cardiovascular Diseasesmentioning
confidence: 93%
“…In contrast, one study of our group on a possible role of virulent strains of H. pylori on patients with idiopathic dysrhythmia showed positive findings [10]. In particular, we found a higher prevalence of both CagA and VacA-positive H. pylori strains in patients with idiopathic dysrhythmia compared to controls [10].…”
Section: Cardiovascular Diseasesmentioning
confidence: 93%
“…This indicated the potential of the pathogen to be linked with conditions now considered "idiopathic". Also, parasitic diseases such as the Trypanosma cruzi-induced Chagas disease need to be revisited, especially under recent developments showing not only that a proportion of these patients present with autoimmune features but also because such patients are also co-infected with H. pylori strains [153] . In addition, other conditions that are now considered to H. pylori is one of the very few infectious agents (along, for example, with Epstein-Barr virus) that have been considered a common denominator in more than 30 autoimmune disorders (Figure 1).…”
Section: Experimental Downsidesmentioning
confidence: 99%
“…One was about the association of Helicobacter cinaedi with atrial arrhythmias, and in the other paper we failed to extract sufficient data [8,15]. Thus, a total of seven studies met the review criteria and were analyzed in our meta-analysis [9,10,16,17,18,19,20]. …”
Section: Resultsmentioning
confidence: 99%
“…In 2005, Montenero et al revealed for the first time a highly significant correlation between H. pylori infection and atrial fibrillation [8]. Other groups also showed that Cag-A positive H. pylori strains were related to idiopathic dysrhythmias [9]. However, Platonov et al have reported no significant association between atrial fibrillation and H. pylori infection [10].…”
Section: Introductionmentioning
confidence: 99%